2017
DOI: 10.1111/dmcn.13597
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating medial gastrocnemius muscle volume in children with spastic cerebral palsy: a cross‐sectional investigation

Abstract: Aim This cross‐sectional investigation evaluates the reliability of estimating medial gastrocnemius anatomical cross‐sectional area (aCSA) in typically developing and spastic cerebral palsy (SCP) cohorts. It verifies whether muscle volume estimations based on aCSA improve when aCSA is multiplied by muscle–tendon unit (MTU) or muscle length, and whether the resulting errors in volume estimations are smaller than changes after intervention. Method Fifteen typically developing children (mean age 8y 2mo [SD 1y 5mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 22 publications
5
70
1
Order By: Relevance
“…Freehand 3DUS has been used to provide reliable measures of MV and ML in both in vitro (Weide et al, ) and in vivo studies of typically developing (TD) children and those with CP (Schless et al, ). Dissected medial gastrocnemius MV and fascicle length from four cadavers showed significantly high correlations with MVs and fascicle lengths measured with 3DUS using a water submersion method and calipers (Weide et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Freehand 3DUS has been used to provide reliable measures of MV and ML in both in vitro (Weide et al, ) and in vivo studies of typically developing (TD) children and those with CP (Schless et al, ). Dissected medial gastrocnemius MV and fascicle length from four cadavers showed significantly high correlations with MVs and fascicle lengths measured with 3DUS using a water submersion method and calipers (Weide et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the article by Schless et al., the ethical commission number was incorrect. It should have been s57384.…”
mentioning
confidence: 99%
“…The work of Schless et al 5 suggests that muscle volume may be estimated from measurements made using a standard two-dimensional (2D) ultrasound scanner. Schless et al reported a strong linear relationship between muscle volume and the product of muscle length and cross-sectional area in the medial gastrocnemius.…”
mentioning
confidence: 99%
“…Schless et al reported a strong linear relationship between muscle volume and the product of muscle length and cross-sectional area in the medial gastrocnemius. 5 This strong relationship has implications for the clinical feasibility of assessing muscle volume in this group. However, the work described is not a complete test of the utility and accuracy of estimating muscle volume by 2D ultrasound.…”
mentioning
confidence: 99%
See 1 more Smart Citation